Pengaruh Penundaan Waktu Pemeriksaan Terhadap Kadar Hemoglobin Metode Kolorimetri - Carolina, Ega; Widiyanto, S.Y Didik; Anung Sugihanto (Jaringan Laboratorium Medis, 2025)
The workload of laboratory staff at the Community Health Center (Puskesmas) is disproportionate to the number of specimens examined, and laboratory equipment is limited. Hemoglobin (Hb) testing is a laboratory test frequently used to support disease diagnosis. Other causes of delays include electrical instability, equipment failure, delayed specimen delivery, shift changes, equipment failure, and excessive blood draws from patients (Ma, Aryandi & Novriani, 2019). This study aimed to determine the effect of the time required for hemoglobin testing using the direct colorimetric method, a 90-minute delay, and a 180-minute delay. This study was a pure experiment using a completely randomized design. The sample consisted of 48 patients, all patients referred to the Plamongan Sari Community Health Center laboratory for hemoglobin testing. The sample had completed informed consent for blood draws. Data analysis included a normality test, which showed a normal distribution, followed by a homogeneity test, which showed a homogeneous data distribution. The results were then analyzed using a one-way ANOVA test at α = 0.05. The study showed no significant difference between hemoglobin levels measured immediately and those delayed by 90 minutes and 180 minutes using the colorimetric method (p-value 0.540). Hemoglobin levels can still be measured after a 90-minute and 180-minute delay. However, it is recommended that samples referred for hemoglobin testing be tested immediately without delay.